The Effect of Greenwashing and Audit Quality on Firm Value: Evidence from High-Carbon-Emission Companies Listed on the Indonesia Stock Exchange - Melati Dwi Agustina; Herawansyah Herawansyah (Eastasouth Institute, 2026)
Growing demands for sustainability reporting have pressured carbon-intensive companies, yet this pressure is often unaccompanied by adequate independent oversight, creating conditions conducive to greenwashing that can undermine the trustworthiness of information relied upon by investors. Grounded in Signaling Theory, this research investigates how greenwashing and audit quality influence firm value among high-carbon-emission firms listed on the Indonesia Stock Exchange between 2021 and 2025, controlling for firm size and leverage. A quantitative design was employed on a purposively selected sample of firms in the energy, basic materials, and industrials sectors, examined through multiple linear regression. Findings reveal that greenwashing exerts a significant negative influence on firm value, implying that discrepancies between environmental disclosures and actual outcomes are interpreted unfavourably by the market. Audit quality shows no significant relationship with firm value, suggesting auditor affiliation has yet to serve as a decisive credibility marker for investors. Firm size shows no meaningful influence, while leverage exerts a positive, significant impact. These results suggest alignment between disclosure and genuine environmental performance carries greater weight in market valuation than auditor prestige. Companies are encouraged to avoid greenwashing to preserve stakeholder trust, while investors are urged to critically evaluate issuers' environmental disclosures before investing.